1996
DOI: 10.3109/00365549609037924
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii in Immunodeficient Subjects by Gene Amplification: Influence of Therapeutics

Abstract: Polymerase chain reaction (PCR) technology was used to detect Toxoplasma gondii DNA in 253 immunodeficient subjects, 179 of whom were infected with the human immunodeficiency virus (HIV). The incidence of toxoplasmosis was 12.3% (22/179) in the HIV-infected subjects and 2.7% (2/74) in the remainder. The sensitivity of the PCR during episodes of toxoplasmosis in HIV-infected subjects not on antiparasitic treatment was 86.6% on peripheral blood and 60% on cerebrospinal fluid (CSF), but was only 25% and 16.7%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
3
18
0
1
Order By: Relevance
“…Furthermore, our data confirmed that a high diagnostic accuracy was achieved when lumbar puncture was performed before or soon after the initiation of antitoxoplasma therapy, whereas the diagnostic sensitivity failed if lumbar puncture was delayed [29]. In agreement with others, no DNA was detected with B1 gene n-PCR in TE patients after >1 week of antitoxoplasma therapy [8,9,34,39,40]. Furthermore, no amplification signal was seen in most of the patients with relapses who were receiving long-term maintenance prophylaxis [38][39][40].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our data confirmed that a high diagnostic accuracy was achieved when lumbar puncture was performed before or soon after the initiation of antitoxoplasma therapy, whereas the diagnostic sensitivity failed if lumbar puncture was delayed [29]. In agreement with others, no DNA was detected with B1 gene n-PCR in TE patients after >1 week of antitoxoplasma therapy [8,9,34,39,40]. Furthermore, no amplification signal was seen in most of the patients with relapses who were receiving long-term maintenance prophylaxis [38][39][40].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with others, no DNA was detected with B1 gene n-PCR in TE patients after >1 week of antitoxoplasma therapy [8,9,34,39,40]. Furthermore, no amplification signal was seen in most of the patients with relapses who were receiving long-term maintenance prophylaxis [38][39][40]. This indicates that the B1 gene has limited value in monitoring the effects of therapy or prophylaxis.…”
Section: Discussionsupporting
confidence: 88%
“…In some series the detection of circulating T. gondii DNA has a good predictive value for patients with cerebral nodules, avoiding invasive procedures, 6 and suggesting that most of the patients with cerebral reactivation have circulating DNA. 12 In contrast, other studies have found only 13% 13 or 25% 14 of patients with cerebral toxoplasmosis to have a positive PCR test in blood. One of the reasons for these discrepancies is that PCR is currently not standardized, especially for prevention of false positive results due to contamination, or false negative results due to inhibitors.…”
Section: Ertemmentioning
confidence: 92%
“…Une PCR sur liquide amniotique, ciblant le gène B1, dans 35 cas et deux PCR sur liquide céphalorachidien chez des immunodéprimés [11] ont été effectuées.…”
unclassified